Digital Storytelling Trends in Early Childhood Education in Indonesia: A Systematic Literature Review - Purnama, Sigit; Ulfah , Maulidya; Ramadani , Laili; Rahmatullah , Bahbibi; Ahmad , Iqbal Faza (Jurnal Pendidikan Usia Dini, 2022)
Digital storytelling is often used in various contexts today, especially in the world of education. Many educators have followed this trend in early childhood education (ECE). This study examines the application of digital storytelling in ECE in Indonesia. Using a systematic literature review (SLR) a method, this research is a qualitative approach which is also known as a meta-synthesis. The literature reviewed was 15 articles from 56 articles that researchers found in the Google Scholar database. The results show that digital storytelling serves as an important method and medium to ensure children's learning experiences are enjoyable. In general, it is used in ECE in Indonesia through simple technology. This technology can enhance a story or fairy tale by making it more fun, interesting, communicative, and dramatic. However, the findings of this review of studies and methodological gaps have implications for ECE policy, practice, and research in Indonesia. Keywords: digital storytelling, early childhood education, storytelling trend in Indonesia References: Agosto, D. E. (2016). Why storytelling matters: Unveiling the literacy benefits of storytelling. Children and Libraries, 14(2), 21–26. Ahmad, I. F. (2022). Urgensi Literasi Digital di Indonesia pada Masa Pandemi COVID-19: Sebuah Tinjauan Sistematis. Nusantara: Jurnal Pendidikan Indonesia, 2(1), 1–18. https://doi.org/10.14421/njpi.2022.v2i1-1 Aisha, I., & Kaloeti, D. V. S. (2021). Digital Storytelling Intervention on Prosocial Behavior Improvement among Early Childhood. Psympathic: Jurnal Ilmiah Psikologi, 7(2), 185–196. https://doi.org/10.15575/psy.v7i2.5713 Boltman, A., & Druin, A. (2001). Children’s storytelling technologies. Differences in Elaboration and Recall. Chambers, G. J., & Yunus, M. M. (2017). Enhancing Learners’ Sentence Constructions via ‘Wheel of Grammar’. Pertanika Journal of Social Sciences & Humanities, 25(4). Davies, D., Jindal-Snape, D., Collier, C., Digby, R., Hay, P., & Howe, A. (2013). Creative learning environments in education—A systematic literature review. Thinking Skills and Creativity, 8, 80–91. Demirbaş, İ., & Şahin, A. (2020). A Systemic Analysis of Research on Digital Storytelling in Turkey. International Journal of Progressive Education, 16(4), 45–65. https://doi.org/10.29329/ijpe.2020.268.4 Dixon-Woods, M. (2010). Systematic reviews and qualitative methods. Qualitative Research: Theory, Method, and Practice. 3rd Edn. London: Sage, 331–346. Egan, K. (1989). Teaching as storytelling: An alternative approach to teaching and curriculum in the elementary school. University of Chicago Press. Gagné, R. M., Briggs, L. J., & Wager, W. W. (1988). Principles of Instructional Design. Holt, Rinehart, and Winston. https://books.google.co.id/books?id=dAsmAQAAIAAJ Gough, D. (2007). Weight of evidence: A framework for the appraisal of the quality and relevance of evidence. Research Papers in Education, 22(2), 213–228. Karlina, D. N., Widiastuti, A. A., & Soesilo, T. D. (2018). Meningkatkan Kemampuan Berbicara Anak Tk B Usia 5-6 Tahun Melalui Digital Storytelling di TK Apple Kids Salatiga. JPUD - Jurnal Pendidikan Usia Dini, 12(1), 1–11. https://doi.org/10.21009//jpud.121.01 Kearney, M., Jones, G., & Roberts, L. (2012). An Emerging Learning Design for Student-Generated" iVideos". Teaching English with Technology, 12(2), 103–121. Kogila, M., Ibrahim, A. B., & Zulkifli, C. Z. (2020). A Powerful of Digital Storytelling to Support Education and Key Elements from Various Experts. International Journal of Academic Research in Progressive Education and Development, 9(2), 408–420. https://doi.org/10.6007/ijarped/v9-i2/7483 Maghfiroh, Suarjana, I. M., & Astawan, I. G. (2020). Pengembangan Media Video Wayang Kreasi Untuk Mendukung Pembelajaran Storytelling Anak Kelompok B Tk Kristen Harapan Denpasar. Indonesian Journal of Instruction, 1(2), 66–75. Malik, M., Altaf, F., & Gull, M. (2020). Challenges Faced by Teachers in Teaching through Storytelling and Play-Way Method at Early childhood Education Level. Global Educational Studies Review, V(III), 152–165. https://doi.org/10.31703/gesr.2020(v-iii).16 Manullang, D., Banjarnahor, H., & Simanjuntak, L. (2021). Developing Digital Story Telling and Educational Games to Improve Early Childhood Cognitive Ability. 6th Annual International Seminar on Transformative Education and Educational Leadership (AISTEEL 2021), 591(Aisteel), 710–718. Maureen, I. Y., van der Meij, H., & de Jong, T. (2018). Supporting Literacy and Digital Literacy Development in Early Childhood Education Using Storytelling Activities. International Journal of Early Childhood, 50(3), 371–389. https://doi.org/10.1007/s13158-018-0230-z Maureen, I. Y., van der Meij, H., & de Jong, T. (2020). Enhancing Storytelling Activities to Support Early (Digital) Literacy Development in Early Childhood Education. International Journal of Early Childhood, 52(1), 55–76. https://doi.org/10.1007/s13158-020-00263-7 Maureen, I. Y., van der Meij, H., & de Jong, T. (2021). Evaluating storytelling activities for early literacy development. International Journal of Early Years Education, 0(0), 1–18. https://doi.org/10.1080/09669760.2021.1933917 Nair, V., & Yunus, M. M. (2021). A systematic review of digital storytelling in improving speaking skills. Sustainability (Switzerland), 13(17). https://doi.org/10.3390/su13179829 Nuraina, Damayanti, E., & Ikawati, A. (2018). Digital Media Dongeng Berbasis Animasi Untuk Pendidikan Karakter Anak Usia Dini. Conference on Innovation and Application of Science and Technology (CIASTECH), 20(2), 177–183. Perry, A., & Hammond, N. (2002). Systematic reviews: The experiences of a PhD student. Psychology Learning & Teaching, 2(1), 32–35. Phillips, L. (2013). Storytelling as Pedagogy. Literacy Learning: The Middle Years, 21(2). Porter, B. (2004). Digitales: The art of telling digital stories. Bernajean Porter. Psomos, P., & Kordaki, M. (2015). A novel educational digital storytelling tool focusing on students’ misconceptions. Procedia-Social and Behavioral Sciences, 191, 82–86. Pusparina, I., Maria, I., & Norfitri, R. (2020). The Effectiveness of Religious Music and Digital Storytelling on the Level of Cooperativeness and Pain in Children During Invasive Treatment (Children’s Room, Zalecha Local Hospital, Martapura). Jurnal Ners, 15(2), 86–90. Rahiem, M. D. H. (2021). Storytelling in early childhood education: Time to go digital. International Journal of Child Care and Education Policy, 15(1). https://doi.org/10.1186/s40723-021-00081-x Robin, B. R. (2008). Digital storytelling: A powerful technology tool for the 21st century classroom. Theory into Practice, 47(3), 220–228. Robin, B. R., & McNeil, S. G. (2019). Digital Storytelling. The International Encyclopedia of Media Literacy, 1–8. Rosyidah, A., & Putri, A. (2019). Digital Storytelling Implementation for Enhancing Students’ Speaking Ability in Various Text Genres. International Journal of Recent Technology and Engineering, 8(4), 3147–3151. https://doi.org/10.35940/ijrte.d8002.118419 Sadik, A. (2008). Digital storytelling: A meaningful technology-integrated approach for engaged student learning. Educational Technology Research and Development, 56(4), 487–506. Shelton, C. C., Archambault, L. M., & Hale, A. E. (2017). Bringing digital storytelling to the elementary classroom: Video production for preservice teachers. Journal of Digital Learning in Teacher Education, 33(2), 58–68. Smith, P. L., & Ragan, T. J. (2005). Instructional Design. John Wiley & Sons. Sulistianingsih, E. (2017). Efektifitas Model Pembelajaran Berbasis Dongeng Digital Untuk Meningkatkan Kecerdasan Emosi Peserta Didik. Jurnal Penelitian Pendidikan, 34(2), 121–126. Tahriri, A., Tous, M. D., & MovahedFar, S. (2015). The impact of digital storytelling on EFL learners’ oracy skills and motivation. International Journal of Applied Linguistics and English Literature, 4(3), 144–153. Tatli, Z., Uğur, N., & Çakiroğlu, Ü. (2018). Peer assessment through digital storytelling: Experiences of pre-service IT teachers. The International Journal of Information and Learning Technology. Tri Aprilia, W., & Hasibuan, R. (2021). Pengaruh Dongeng Digital Terhadap Kemampuan Kosakata Bahasa Jawa Krama Anak Usia 5-6 Tahun di Tk Dharma Wanita Ngimbang Lamongan. Jurnal Pendidikan Indonesia, 2(7), 1283–1294. https://doi.org/10.36418/japendi.v2i7.230 Tridinanti, G. (2017a). English Introduction Through Digital Storytelling in Early Childhood. Ijlecr - International Journal of Language Education and Culture Review, 3(1), 49–55. https://doi.org/10.21009/ijlecr.031.06 Tridinanti, G. (2017b). Enhancing Children’S English Vocabulary Acquisition Through Digital Storytelling of Happy Kids Kindergarten of Palembang. International Journal of Educational and Pedagogical Sciences, 11(11), 2727–2730. https://doi.org/doi.org/10.5281/zenodo.1314514 Wahyuni, W., Sujoko, S., & Sarosa, T. (2018). Improving Students’ Speaking Skill Through Project-Based Learning (Digital Storytelling). English Education, 6(2), 161–168. Yordan, A., & Fahyuni, E. F. (2021). Child-Friendly IRE Learning Through Digital Storytelling in the COVID-19 Pandemic. Nazhruna: Jurnal Pendidikan Islam, 4(3), 590–605.